Studi Perbandingan Analisis Gaya Gempa Terhadap Struktur Gedung Di Kota Madiun Berdasar SNI 1726 2002 dan RSNI 201X - Kholilur Rohman, Rosyid (JURNAL AGRI-TEK, 2014)
Planning a building should refer to regulations on the procedures and rules that apply. It's been done socializing RSNI-03-1726-201X which regulates Standar Perencanaan Ketahanan Gempa untuk Struktur Bangunan Gedung as substitution to SNI-03-1726-2002. The implications of new standart for building need to be done for research. In this study, made building structure model 5 floors with a size 24 x 24 m2. The location of the building in Madiun city and its function as an office. The structure is analyzed with SNI 03-1726-2002 and RSNI-03-1726-201X so that known changes of earthquake load value, distribution of earthquake load on each level, internal force and displacement. Analysis of the structure used ETABS version 9. Results of the analysis shown that earthquake load according to SNI 1726 201X bigger around 27.5% and the distribution of load more bigger on each floor. Internal forces more bigger around 27,67 % in column structure and more bigger 28,56 % on beam structure. Displacement of structure more bigger about 27,99– 30,92 %.Keywords : earthquake load, analysis of structure, internal force, dispalcement